Communication between Plants and Rhizosphere Microbiome: Exploring the Root Microbiome for Sustainable Agriculture - Ben Jesuorsemwen Enagbonma; Ayomide Emmanuel Fadiji; Ayansina Segun Ayangbenro; Olubukola Oluranti Babalola (Microorganisms, 2023)
Plant roots host numerous microorganisms around and inside their roots, forming a community known as the root microbiome. An increasing bulk of research is underlining the influences root-associated microbial communities can have on plant health and development. However, knowledge on how plant roots and their associated microbes interact to bring about crop growth and yield is limited. Here, we presented (i) the communication strategies between plant roots and root-associated microbes and (ii) the applications of plant root-associated microbes in enhancing plant growth and yield. This review has been divided into three main sections: communications between root microbiome and plant root; the mechanism employed by root-associated microbes; and the chemical communication mechanisms between plants and microbes and their application in plant growth and yield. Understanding how plant root and root-associated microbes communicate is vital in designing ecofriendly strategies for targeted disease suppression and improved plant growth that will help in sustainable agriculture. Ensuring that plants become healthy and productive entails keeping plants under surveillance around the roots to recognize disease-causing microbes and similarly exploit the services of beneficial microorganisms in nutrient acquisition, stress mitigation, and growth promotion.